Clinical features and surgical treatment of sacral schwannomas - Pan, Weibo (Oncotarget, 2017)
BACKGROUND: Sacral schwannoma is relatively rare and both the early diagnosis and appropriate treatment of sacral schwannomas are equally very challenging. METHODS: 11 sacral schwannoma cases operated at the Second Affiliated Hospital, School of Medicine, Zhejiang University, from 2012 to 2016, were investigated retrospectively and 10 were followed up. All patients were assessed with X-ray, CT and MRI, and underwent an intralesional excision. RESULTS: One patient was male, nine were female and the average age was 48 (ranging between 31 and 63). Three patients suffered from back and leg pain, and seven had no obvious symptoms. The average blood loss during surgery was 980ml (ranging between 100 and 2,000ml). Six patients underwent preoperative biopsy. The surgeries were performed via the combination of an anterior and posterior approach in two patients, a posterior approach in seven patients, and an anterior approach in one patient. Residual tumors were not detected in all patients after surgery. Unfortunately, the postoperative complications occurred in three patients, namely bowel and bladder dysfunction (two patients) and cerebrospinal fluid leakage with secondary intracranial infection (one patient). The average follow-up was 22.7 months (8-44 months). All patients were relieved from preoperative symptoms after the last follow-up. CONCLUSIONS: The typical findings of our cases in MRI were a well-circumscribed lesion with a heterogenous signal intensity on T2-weighted image, which may be helpful for preoperative decision-making. Intralesional excision can be successfully performed using single anterior or single posterior or both, and is an important procedure in the treatment of sacral schwannomas.